THE EFFECT OF APPLICATION OF AUDIT DIGITALIZATION ON AUDITOR PERFORMANCE WITH PROFESSIONAL ETHICS AS A MODERATION VARIABLE : (Survey on KAP in Central Java) - Dewi Saptantinah Puji Astuti; Uliya Rohmah (Transpublika Publisher, 2023)
In recent years, digitalization has transformed various aspects of business operations, including the field of auditing. The integration of digital technologies in audit processes has the potential to enhance efficiency, accuracy, and overall performance. As organizations increasingly adopt digital audit practices, it becomes essential to examine the impact of digitalization on auditor performance. The objective of this research is to assess the impact of digitalization audits on auditor performance. The study focuses on a public accounting firm located in Central Java, comprising a total of 24 individuals. Primary data was collected for this research. The population considered was the entire group of auditors working in public accounting offices in Central Java. Purposive sampling method was employed, resulting in a sample size of 60 auditors. Data was collected through questionnaires distributed directly to auditors in the public accounting offices in Central Java. Multiple linear regression analysis was used to analyze the data. The data analysis techniques included classic assumption testing, multiple linear analysis, t-test, F-test, coefficient determination (R2), and regression analysis with a moderating variable. The results of the research indicate that audit digitization has a significantly positive influence on auditor performance. However, professional ethics was found to have no moderating effect on the influence of audit digitization on auditor performance in public accounting firms in Central Java.